The Effect of Working Capital Management Efficiency on the Operating Performance of the Industrial Companies in Oman - Jamil, Syed Ahsan; Al Ani, Mawih Kareem; Al Shubiri, Faris Nasif (International Journal of Economics and Financial Issues, 2015)
The aim of this study is to examine the effect of working capital management efficiency on the operating performance of industrial companies listed in the Muscat Securities Exchange (MSM) in Sultanate of Oman. The study employed an explanatory non-experimental research design. 37 out of 48 industrial companies listed in the MSM were taken. The study used the data contained in the annual reports of these companies for the period 2009-2013. The working capital management efficiency is measured working capital ratios such as cash conversion cycle (CCC), current ratio (CR), current assets turnover (CAT), net working capital ratio (NWCR), while the operation performance is measured by net operating profit (NOP) and earnings before interest and tax (EBIT). The regression results revealed that the first model is significant and there are only CCC and NWCR have impact on the NOP, but the second model is insignificant. Keywords: Working Capital Management Efficiency; Operating Performance; Working Capital Ratios JEL Classifications: G30; G32; L25